Descriptions of rajid egg cases from southeastern Australian waters - Treloar, M. A.; Laurenson, L. J.b.; Stevens, J. D. (Zootaxa, 2006)
Egg cases from nine skate species occurring in Tasmanian waters were examined and measured. A species-specific identification key is provided for eight of these species. The key was developed primarily from fresh egg cases dissected from the oviduct, although specimens collected from the ocean floor or found dried on the beach were also used to test the key. Egg cases for the ninth species could not be included because the only egg case pair recovered was partially formed. A diagnosis of the posterior end of this egg case is provided.